A delicate calculation method for reservoir initial water saturation based on a novel approach to J-function construction - Xiongzhi Liu; Hao Yang; Yongqiang Qu; Liang Hong; Lifei Dong; Hao Kang (PLoS ONE, 2025)
Accurately determining initial water saturation is essential for assessing reservoir resources and optimizing development, yet conventional J-function methods face challenges such as variability in curve fitting due to sample heterogeneity, less-than-optimal grouping schemes, and limited core sample availability. This study addressed these issues by analyzing 55 J-function curves from the N reservoir in Iraq’s Zagros Basin, identifying permeability as the primary factor influencing curve shape. A novel classification method was developed, categorizing curves into power function and exponential function types based on permeability thresholds. Improved J-function models were established by correlating undetermined coefficients with the reservoir quality index (RQI), enabling continuous, tailored calculations, eliminating the need for sample grouping. Case studies demonstrated that the improved J-function method provides more accurate water saturation (Sw) estimates in Reservoir N (porosity 0.1–0.27) compared to the Archie equation and conventional J-function: (1) In high-quality intervals (e.g., 3682–3683 m), it yields Sw = 0.06–0.11, closely matching core-derived irreducible water saturation (0.1), while Archie overestimates Sw (0.23–0.74); (2) In poor-quality zones (3676.5–3681 m), it agrees with Archie’s Sw but corrects the conventional J-function’s underestimation by accounting for subtle property variations. These advancements provided a robust framework integrating permeability-based J-function classification, RQI-correlated coefficient models, and continuous saturation calculations, eliminating the need for sample grouping.